The Inclusion of Literature Components in Malaysian English Papers: the Challenges and Pros in Teaching and Learning - Yahya Omar (Institut Agama Islam Negeri Imam Bonjol Padang, 2017)
The low proficiency attainment in English language among Malaysian learners has been given main attention in Malaysia Ministry of Education’s plan to further improve education. Part of the plan is by introducing literature components in the teaching and learning of English language curriculum. This has immediately changed the scenario of teaching and learning in English language classroom. This paper will review past studies related to the implementation of Literature component in English language by looking specifically at the teacher’s roles since teachers are the direct factor contributor in learners’ process of learning and teaching. Apart of roles in the learning process, teachers’ approaches employed in teaching literature component will be critically reviewed in this paper and suitable approaches available in teaching literature in English will be put forward.